PERANCANGAN SISTEM INFORMASI PENJUALAN KERAJINAN AKRILIK BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK CODEIGNITER PADA TOKO CRAFT SEASON - Adella Rifiandika Putri (2022)
The sale of acrylic crafts is currently in great demand by many circles, especially lovers of acrylic art. In addition to the variegated acrylic glass models, this craft can also be combined with various other unique creativity such as handwriting, polaroid photos, lights and so on. Craft Season stores have not used the information technology that is developing at the moment. In the process of sales calculation transactions still using a calculator, this allows errors to occur due to the carelessness of the owner in entering numbers. In addition, all transactions are still carried out by recording on the sales report book. This is not effective because it is likely that errors can occur due to the loss of books or human error and inefficient use of paper. Then there is no availability of product stock data that informs the price, category, description and number of stocks, so the owner has difficulty in seeing or searching for the product. Therefore, information technology is needed to create a web-based system using the CodeIgniter framework conducted in this study. The research methodology used for system development is the Waterfall method as well as the creation of a Unified Modelling Language (UML) for system design. The results obtained are a Craft Season Store Sales website that can be run according to all its functions. With this web, it is hoped that it can help both for admins in managing product data and order data as well as customers who will make purchases and transactions.